Mimicking uterine malignancy: Pelvic actinomycosis with giant uterine leiomyoma. (2021) - Li, Changzai; Zhang, Pan; Jiao, Guimei; Lv, Jie; Ma, Chunmei; Song, Xudong; Zhang, Jinji; Wu, Chuntao; Li, Ruiwei; Zhu, Hongcheng
Abstract: Pelvic actinomycosis is a rare disease which is hard to be distinguished from other diseases such as malignant tumors and tuberculosis due to its nonspecific clinical signs and symptoms. If pelvic actinomycosis can be diagnosed preoperatively, the patients can be cured with antimicrobial therapy avoiding surgery. It is especially of concern to distinguish pelvic actinomycosis from pelvic mass, if there is a history of intrauterine device use. We report a case of pelvic actinomycosis that was diagnosed after the postoperative pathology of a suspected uterine malignancy.